Using FaceReader to explore the potential for harnessing emotional reactions to motivate hand hygiene. Issue 3 (May 2022) - Rutter, Sophie; Bonne, Marc; Stones, Catherine; Macduff, Colin
Background: Handwashing is a key strategy for reducing the spread of infection but hand hygiene practises are often poor. Pre-testing messages prior to a campaign is expensive and time consuming. Objective: This study investigates (1) emotional reactions to handwashing messages based on four different theoretical constructs (Knowledge of Risk, Comfort, Disgust and Social Norms), (2) how images may influence emotional reactions and (3) the influence of emotion, images and theoretical construct on handwashing motivation. Methods: A novel methodology was employed whereby FaceReader, software that automatically analyses emotions, was used to identify reactions to handwashing messages. Thirty-one participants from The University of Sheffield were recruited for this laboratory study. Results: Most participants did not react strongly to any message and emotional reactions were similar for messages from different theoretical constructs. Adding images to text messages intensified some emotional reactions, particularly Happy and Disgusted for the two messages from the Disgust theoretical perspective. Moreover, participants thought that messages that used images were 1.8 times more likely to encourage handwashing. Knowledge of Risk messages (most encouraging) were 2.9 times more likely to be selected as encouraging handwashing than Comfort messages (least encouraging). An increase in the Disgusted emotion was also associated with an increase in encouragement. Discussion: This study suggests that handwashing messages should be designed to exploit emotional reactions but more research is needed to understand how to design messages for these reactions. Whether disgust is as important post Covid-19 requires future investigation. FaceReader can be usefully and inexpensively employed to pre-test handwashing messages.